MAKNA SESAJEN DALAM RITUAL NYEKAR MAKAM KYAI LANGSUR DI DUSUN KLURAHAN KECAMATAN SUKOHARJO KABUPATEN SUKOHARJO - Nisma Dwi Yulikartika Prasetyaningrum; Agus Efendi; Tri Widiatmi; R. Adi Deswijaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the symbolic meaning of offerings (sesajen) in the nyekar ritual at the tomb of Kyai Langsur located in Klurahan Hamlet, Sukoharjo District, Sukoharjo Regency. The nyekar tradition accompanied by offerings is one of the cultural and spiritual practices of Javanese society that is still preserved today. This research uses a qualitative approach with a descriptive method. Data were collected through field observations, in-depth interviews with the tomb caretaker, local residents, and pilgrims, as well as documentation of ritual activities. The validity of the data was tested through source triangulation and technique triangulation, while data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The results of the study show that the offerings in the nyekar ritual contain symbolic meanings that are collectively understood by the community as a medium for conveying prayers, good intentions, gratitude, and respect for ancestors. Each element of the ubo rampe (ritual offerings) has its own meaning representing values of purity, sincerity, inner peace, and spiritual readiness in prayer. The series of nyekar rituals, starting from the preparation of offerings, the procession around the village, to the collective prayer at the tomb, forms a unified symbolic meaning that reflects the spiritual relationship between humans, God, and ancestors. This tradition also represents local wisdom and the cultural identity of the Javanese community that continues to be preserved.